Aktivitas Antioksidan Teh Herbal Dari Campuran Daging Buah Pare (Momordica charantia L.), Jahe Merah (Zingiber officinalle Roscoe) Dan Temulawak (Curcuma xanthorrhiza Roxb) - Musyirna Rahmah Nasution; Syamira (Sistem Informasi, 2020)
Herbal tea is a formulation of herbal flowers, seeds, leaves, roots, and bark of various plants. It has affectiveness in energizing, healing constipation and approving immune. It has been done an experiment of antioxidant activity of herbal tea from the mixture of bitter melon (Momordica charantia L), red ginger (Zingiber officinale Roscoe) and curcuma (Curcuma xanthorrhiza Roxb). The purpose of this experiment is to make formulation of herbal tea that has strong antioxidant activity and preferably from a mixture of bitter melon (Momordica charantia L), red ginger (Zingiber officinale Roscoe) and curcuma (Curcuma xanthorrhiza Roxb) that has been dried at a temperature of 50-60°C.The activity of antioxidant is measured by DPPH method, meanwhile organoleptic is analyzed by hedonic method. The result of the experiment from 4 formulations indicates that high antioxidant activity is FIII based on analysis one way ANOVA and Tukey test 99% true. The compositions of FIII are 1,25 g bitter melon, 0,375 g red ginger and 0,375 g curcuma has high antioxidant in 97,25%. Hedonic test indicates FIII in liking category after added 2 g palm sugar and 5mL lemon.